2023
DOI: 10.1002/jmv.28603
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of herpes simplex virus type 2 in the Middle East and North Africa: Systematic review, meta‐analyses, and meta‐regressions

Abstract: Herpes simplex virus type 2 (HSV-2) infection is a prevalent, sexually transmitted infection with poorly characterized prevalence in the Middle East and North Africa (MENA) region.This study characterized HSV-2 epidemiology in MENA. HSV-2 reports were systematically reviewed as guided by the Cochrane Collaboration Handbook and findings were reported following PRISMA guidelines. Random-effects meta-analyses and metaregressions were performed to estimate pooled mean outcome measures and to assess predictors of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The HSV-2 seroprevalence among the general population is 7.9% (6.9-8.8%), similar to the overall prevalence of HSV-2 in Asia, 21 lower than in Europe, Sub-Saharan Africa, and Australia but higher than the Middle East and North Africa. 8,10,12,13,30 With other regions whose prevalence was flat 8 or increasing 10,11 , we observed the HSV-2 prevalence in China reduced by about 2% every five years, which could be attributed to better STI clinic access and improved STI education among the general population nationwide. 31,32 Stratified by sex, we observed comparable HSV-2 prevalence between men and women.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The HSV-2 seroprevalence among the general population is 7.9% (6.9-8.8%), similar to the overall prevalence of HSV-2 in Asia, 21 lower than in Europe, Sub-Saharan Africa, and Australia but higher than the Middle East and North Africa. 8,10,12,13,30 With other regions whose prevalence was flat 8 or increasing 10,11 , we observed the HSV-2 prevalence in China reduced by about 2% every five years, which could be attributed to better STI clinic access and improved STI education among the general population nationwide. 31,32 Stratified by sex, we observed comparable HSV-2 prevalence between men and women.…”
Section: Discussionmentioning
confidence: 69%
“…7 Recent meta-reviews have reported a wide range of prevalence estimates from different geographical regions, including 37.3% in sub-Saharan Africa, 8 20.6% in Latin America, 9 15.4% in Canada, Australia, and New Zealand, 10 12.4% in Europe, 11 12.1% in Asia, 12 and 5.1% in the Middle East and North Africa among the general population. 13 Seroprevalences of HSV-2 among key populations such as male sex workers(MSW), men who have sex with men (MSM), and female sex workers (FSW) are substantially higher across regions, ranging from 20.6% to 74.8% for FSW and from 18.3% to 54.6% for MSM and MSW. [8][9][10][11][12][13] Despite the existing literature, a comprehensive overview of HSV-2 epidemiology and trends among different populations in China is limited, calling for a systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of the standardized methodology used in updating the previously conducted systematic reviews for Asia [1, 2], Europe [3, 4], Latin America and the Caribbean [5, 6], Middle East and North Africa [7, 8], sub-Saharan Africa [9, 10], and for Canada, Australia, New Zealand, and Pacific Island nations [1113].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Genital herpes is a common sexually transmitted infection characterized by painful genital blisters or ulcers, with an estimated 491 million (13%) people aged 15-49 years affected worldwide [1][2][3][4]. It is mainly caused by herpes simplex virus type 2 (HSV-2) and more rarely by HSV type 1 (HSV-1).…”
Section: Introductionmentioning
confidence: 99%